Photon Counting Based on Solar-Blind Ultraviolet Intensified Complementary Metal-Oxide-Semiconductor (ICMOS) for Corona Detection - Yan Wang; Yunsheng Qian; Xiangyu Kong (IEEE Photonics Journal)
For the detection of weak signals, photon counting technology has attracted much attention. In this paper, a method based on photon counting is experimentally demonstrated to realize corona discharge detection at solar-blind ultraviolet (UV) wavelength. In our setup, a solar-blind UV optical filter and a Te-Cs cathode are used to eliminate the effects of light with undesired wavelengths, i.e., outside of the solar-blind band. A two-stage microchannel plate with a high voltage can achieve a gain of up to 106. A phosphor screen coupled with a CMOS can capture complete images without image distortion. By using an ICMOS, the setup can detect single-photon events. Then, applying photon counting statistics, a theoretical probability model of the photon numbers is obtained. Meanwhile, through analyzing the structure of the photon events considering both pixel and temporal resolution, two photon counting algorithms are proposed. Through experiments with an UV light source, the algorithm based on temporal resolution is proved to be more accurate. Finally, through an experiment with a corona discharge device, a solar-blind photon counting image is captured, and the photon number is calculated through the proposed counting algorithm. The probability curve of the practical photon numbers is acquired via several experiments carried out at the same conditions, which proves the accuracy of the setup and algorithm when compared with the theoretical probability model. Therefore, the proposed method can provide a scientific evaluation for corona detection.